KORONER REVASKÜLARİZASYON İÇİN KULLANILAN POMPALI VE POMPASIZ YÖNTEMLERİN ERKEN DÖNEM SONUÇLARININ KARŞILAŞTIRILMASI - KÖKSAL, Cengiz; ÇÖRTELEKOĞLU, Ahmet Tansel; ALTAN, Seyfettin Hakan; SARIKAYA, Sabit; ÖZCAN, Vural; ZENGİN, Mustafa (Cerrahpaşa Medical Journal, 2019)
Background and Design.- Whether the clinical outcomes of off-pump coronary artery bypass grafting surgery is superior to on-pump coronary arter surgery is still a matter of debate. The aim of this clinical prospective study was to compare the early-term results of off-pump and on-pump techniques for myocardial revascularization. Between 2001 and 2003, 100 patients who needed myocardial revascularization was scheduled to be operated with either conventional technique (n: 50) or off-pump technique (n: 50). In the postoperative period, both groups were compared in terms of blood urea, creatinine, SGOT, SGPT levels, need for (+) inotrop agents, ventilation time, amount of blood and blood products transfusion, hospital and intensive care unit stay and amount of drainage. Results.- Statistically significant difference was found between the two groups, favoring off-pump coronary revascularization, with respect to intensive care unit stay, ventilation time, need for (+) inotropic agents, and hepatic enzyme (SGOT, SGPT) levels in the postoperative early period. Conclusion.- Off-pump coronary revascularization offers important clinical advantages in the early postoperative period compared to conventional technique. However, long-term follow-up is required to assess the future effectiveness of off-pump technique.